El uso de la plataforma Zoom y la incidencia en el desempeño laboral de los docentes de la Unidad Educativa Batzacón, en el período académico 2020-2021. - Duchi Ushca, Deisy Maribel (2021)
The present research work of the National University of Chimborazo Commercial Engineering Career is the use of the Zoom platform and the impact on the work performance of the teachers of the Batzacón Educational Unit in the academic period 2020-2021, where it was determined the relevant objectives to try to solve the problem. The incidence of the use of the Zoom platform on the work performance of the teachers of the Batzacón Educational Unit is also shown. Within the State of the Art and theoretical framework, investigations were carried out in different bibliographic sources supporting the investigation with several definitions of the topic or problem. In the Methodology, the hypothetical-deductive method was determined; the type of research is descriptive and explanatory. We worked with the total population since the sample was not calculated because it is less than 100, for the data collection, the survey technique was used through the questionnaire instrument that was directed to the teachers of the Batzacón Educational Unit Finally, for data processing and analysis, Microsoft Excel and SPSS statistical software were used. For the correct analysis and interpretation of the results, the information was presented through graphs and statistical tables; in addition, the hypothesis verification was carried out using the Chi-Square test, thus obtaining that the use of the Zoom platform does affect the work performance of the teachers of the Batzacón Educational Unit, with the results obtained we proceed to establish the conclusions and recommendations. To conclude, strategies are proposed to improve the job performance of the teachers of the Batzacón Educational Unit through the use of the Zoom platform.